Effect of Lactobacillus rhamnosus AB-GG combined with phototherapy on neonatal jaundice indicators, intestinal microbiota and metabolism - Yuan, Yanhan; Chen, Jiayi; Liu, Tianyu; Chen, Juanjuan; Zhang, Feng; Shi, Zhe; Zhang, Jinping (Frontiers in Nutrition, 2025)
ObjectivesTo assess whether Lactobacillus rhamnosus AB-GG supplementation has a treatment effect on the neonatal jaundice of infants receiving phototherapy.MethodsIn this study, 11 and 10 neonates in experimental and control groups were recruited, respectively (upon the follow-up of experimental groups at 7–14 days after discharge, stool frequency was decreased commonly. Therefore, this study was prematurely terminated). After 12 h of phototherapy, researchers recorded clinical information and measured transcutaneous bilirubin (TCB). Fresh fecal samples were collected at seven specific time points: before phototherapy (A), after 12 (B), 24 (C) and 36 h (D) of phototherapy, as well as 10 (D10), 20 (D20) and 30 days (D30) after delivery.ResultsA tendency toward fewer blue light sessions and shorter time of hospitalization was shown in experimental groups, but this exhibited no statistical significance (p > 0.05). Compared with the experimental groups, phototherapy significantly reduced the alpha (α) diversity of intestinal flora in the control groups. However, phototherapy had no significant effect on beta (β) diversity between experimental and control groups. This study also observed that the metabolic composition structures of both groups underwent changes before and after phototherapy. However, no significantly differential metabolites were identified when the groups were compared at different time points.ConclusionLactobacillus rhamnosus supplementation was shown to mitigate intestinal dysbiosis in jaundiced neonates, which thereby facilitated a more rapid recovery of gut microbiota depleted by phototherapy.Clinical trial registerIt was registered with the Chinese Clinical Trial Registry (Registration No.: ChiCTR2000036013).